PERSEPSI MASYARAKAT TERHADAP KEAMANAN DAN MANFAAT TERAPI KOMPLEMENTER PADA PASIEN STROKE - Ade Sucipto; Yayat Supriyatna; Sri Rahayu (JKM-Bid: JURNAL KESEHATAN MASYARAKAT KEBIDANAN (The Journal of Public Health Midwifery), 2026)
Stroke is one of the leading causes of disability that requires long-term treatment and rehabilitation. In addition to medical treatment, complementary therapy is increasingly used by the community as supportive therapy for stroke patients. However, public understanding regarding the safety and benefits of complementary therapy is still varied. This study aimed to determine public perceptions regarding the safety and benefits of complementary therapy in stroke patients. This study used a quantitative descriptive design with a purposive sampling technique involving 60 respondents. Data were collected using questionnaires on public perceptions regarding the safety and benefits of complementary therapy in stroke patients. The complementary therapies discussed in this study included cupping therapy, massage, herbal therapy, acupressure, and other traditional therapies. The results showed that perceptions regarding the safety of complementary therapy were mostly in the sufficient category with 28 respondents (46.7%), while 21 respondents (35.0%) had good perceptions and 11 respondents (18.3%) had poor perceptions. Perceptions regarding the benefits of complementary therapy were also mostly in the sufficient category with 27 respondents (45.0%), while 24 respondents (40.0%) had good perceptions and 9 respondents (15.0%) had poor perceptions. Respondents stated that complementary therapy could help reduce muscle stiffness, improve relaxation, and increase comfort in stroke patients. However, some respondents still doubted the safety and effectiveness of complementary therapy due to limited information and understanding. The study concludes that public perceptions regarding the safety and benefits of complementary therapy in stroke patients are still varied. Therefore, health education from health workers, especially nurses, is needed to improve public understanding regarding the safe and appropriate use of complementary therapy in stroke patients.